Evaluation of energy and protein intake and prediction of growth performance of growing-finishing pigs based on meta-analysis - DI Hanqiu; WANG Shanshan; ZHONG Yifan; CHEN Bin; WANG Haifeng (浙江大学学报. 农业与生命科学版, 2024)
A meta-analysis method was used to integrate the results of 112 literatures from 2002 to 2022. Three functional models (polynomial function, power function and Bridges function) were fitted to estimate the daily digested energy intake (DEI) and crude protein intake (CPI) of Chinese growing-finishing pigs, and to predict the functional relationship between the body mass, dietary DEI and CPI, and growth performance indexes. The results showed that all the three functional models provided a reasonable fit for the DEI and CPI, and the polynomial function had a greater goodness of fit than did the power function and Bridges function. The predicted values of the DEI of the polynomial function and Bridges function were slightly higher than those of the Nutrient Requirements of Swine published by the National Research Council (NRC) in 2012 [referred to as NRC (2012)], while the predicted values of the CPI of the three functions were slightly lower than or close to those of NRC (2012). The results of this study can be helpful to develop feeding plans which are more in line with the nutritional requirements of growing-finishing pigs, and to provide reference for the formulation of feed for pigs, so as to improve feed utilization efficiency and reduce the feeding cost of pigs.